Loss control auditing a guide for conducting fire, safety, and security audits - Dunlap, E. Scott (CRC Press, 2011)
"A comprehensive resource for those developing and executing a loss control audit program, this book comes at the material from three perspectives: Workplace safety, physical security, and life safety and fire service. Written for professionals in loss prevention and safety management as well as those studying the field, this reference includes core auditing issues that are addressed in the mainstream by loss control professionals and provides insight on the implementation of an auditing program within organizations. It illustrates audit scoring methodologies and presents sample audit formats for reader understanding and future use"-- Provided by publisher.
Keywords: Fire prevention -- Inspection.; Industrial buildings -- Fires and fire prevention.; Loss control.; Industrial safety.; elektronické knihy; electronic books